Factors affecting slip and stress distribution of concrete slabs in composite beams. (15th October 2021) - Kamar, Ahmed; Lasheen, Mahmoud; Shaat, Amr; Zaher, Amr; Khalil, Ayman
Highlights: The channel shear connectors are usually stiffer than the angle shear connectors in resisting the slip of concrete slab by about 30% within the elastic range. Increasing the reinforcement ratio of the concrete slab from 0.18% to 0.46% increases the flexural strength of the composite beams by 7.45% and the deflection values were dropped by 23%. Using upper steel reinforcement mesh prevented any longitudinal cracks at the top surface of the concrete slab and allowed for full plastification of the steel cross-sections. Poisson's ratio of the concrete slab was found constant throughout the test with a value of 0.16 and dramatically increases before failure occurs. Abstract: An experimental program is carried out to examine the effects of different factors on the slip and stress distribution of concrete slabs in composite beams. A total of ten steel–concrete composite beams with a span of 4.80 m are tested to find the effects of the type of shear connectors and the concrete slab reinforcement on the behaviour of composite beams. All beams consist of monosymmetric steel cross-sections connected to 120 cm wide concrete slabs. Welded shear connectors (angles or channels) spaced at 20 cm are used to connect the concrete slabs to the steel beams. The concrete slabs of eight beams are provided with a lower steel reinforcement only while two beams are provided with both lower and upper steel reinforcement. The results showed that the ultimate load capacity of composite beam with channel connectors is 14% higher than the counterpart beam with angle connectors and 30% stiffer in resisting the slip of the concrete slab. Moreover, composite beams with channel connectors tend to maintain strain compatibility at the interface between concrete slab and steel section better than the counterpart beams with angle connectors. It is also found that using upper steel reinforcement mesh enhances the stress distribution in the concrete slab until failure. It is found that increasing the reinforcement ratio of the concrete slab from 0.18% to 0.46% increases the flexural strength of the composite beams by 7.45%, while decreases the deflection values by 23%. Moreover, using upper steel reinforcement prevented the longitudinal cracking of the top surface of the concrete slab and allowed for full plastification of the steel cross-sections.